Collective action against sexism in Germany, Turkey, and Japan: The influence of self-construal and face concerns - ZAMANTILI NAYIR, DİLEK (SAGE PUBLICATIONS LTD, 2017)
We suggest that self-construal and face concerns influence individuals' collective action intentions against sexism. We examined female students from Germany (N = 105), Japan (N = 112), and Turkey, (N = 111), exposed them to a benevolent and a hostile sexism scenario, and compared their collective action intentions and indirect conflict management styles (avoiding, outflanking) within countries. As predicted, German and Turkish female students' collective action intentions against sexism surpassed their intentions for indirect conflict management styles, whereas the reverse was true for Japanese female students. However, Japanese female students had an unaccomplished desire for collective action, suggesting that they wish to act but decide against open confrontation to maintain ingroup harmony. The higher individuals' independent self-concept and the less they value face, the higher their collective action intentions against hostile sexism in all three countries. We discuss culturally appropriate ways of collective action.
Keywords: ambivalent sexism; benevolent sexism; collective action; face culture; hostile sexism; independent self; interdependent self; BENEVOLENT SEXISM; PATERNALISTIC LEADERSHIP; MEASUREMENT EQUIVALENCE; CONFRONTING SEXISM; SOCIAL COSTS; GENDER; PREJUDICE; CONFLICT; CONSEQUENCES; RESPONSES